Effects of plant traits on caterpillar communities depend on host specialisation. Issue 6 (13th June 2021) - Abe, Tomokazu; Volf, Martin; Libra, Martin; Kumar, Rajesh; Abe, Haruka; Fukushima, Hiroaki; Lilip, Roll; Salminen, Juha‐Pekka; Novotny, Vojtech; Kamata, Naoto; Murakami, Masashi
Abstract: The community composition of insect herbivores is largely shaped by host–plant phylogeny and functional traits. These effects differ between herbivores due at least in part to varying levels of diet specialisation. Distinguishing between herbivores with differing specialisation is therefore necessary to understand the roles of host phylogeny and traits in shaping complex insect communities. We surveyed the complete plant–caterpillar food web in a 0.2 ha plot of a lowland cool‐temperate deciduous forest. We measured leaf nutrients, physical traits and polyphenols of the hostplants and analysed the effects of leaf traits and phylogeny on Lepidoptera caterpillars with differing levels of host specialisation. We sampled 190 species from 16 433 individual caterpillars on 20 host plant species. These included 102 species of specialists using confamilial hostplant species, 17 species of conservative generalists using allofamilial but phylogenetically close hostplant species and 71 species of non‐conservative generalists using phylogenetically distant hostplant species. The species composition of non‐conservative generalists associated with the polyphenol protein precipitation capacity and overall leaf trait dissimilarity; conservative generalists were weakly associated with polyphenol oxidative activity. In contrast, the composition of specialist assemblages showed no correlation with leaf traits. Our results demonstrate that host phylogeny and traits play variable roles in structuring communities of herbivores, based on the phylogenetic specialisation of herbivores. Understanding the factors that shape the community structures of various herbivores traditionally classified as 'generalists' is important as they account for a large proportion of herbivore species while showing differential responses to traits of hosts. Abstract : The complete plant–caterpillar food web in a 0.2 ha plot of a cool‐temperate deciduous forest were surveyed. Twenty species from 12 families of plants were included. This enabled us to investigate the role of plant traits as drivers of caterpillar community composition in a forest plot scale, quantifying a broad spectrum of host plant specialisation. We found generalist species exhibiting phylogenetically indiscriminate host use accounted for a large share of individuals. Understanding factors that shape their community will be important in temperate forests.